New estimates and synthesis of chromosome numbers, ploidy levels and genome size variation in Allium sect. Codonoprasum: advancing our understanding of the unresolved diversification and evolution of this section - Kobrlová, Lucie; Jandová, Michaela; Vojtěchová, Kateřina; Šafářová, Lenka; Duchoslav, Martin (Botanical studies, 2024)
BACKGROUND: The genus Allium is known for its high chromosomal variability, but most chromosome counts are based on a few individuals and genome size (GS) reports are limited in certain taxonomic groups. This is evident in the Allium sect. Codonoprasum, a species-rich (> 150 species) and taxonomically complex section with weak morphological differences between taxa, the presence of polyploidy and frequent misidentification of taxa. Consequently, a significant proportion of older karyological reports may be unreliable and GS data are lacking for the majority of species within the section. This study, using chromosome counting and flow cytometry (FCM), provides the first comprehensive and detailed insight into variation in chromosome number, polyploid frequency and distribution, and GS in section members, marking a step towards understanding the unresolved diversification and evolution of this group. RESULTS: We analysed 1578 individuals from 316 populations of 25 taxa and reported DNA ploidy levels and their GS, with calibration from chromosome counts in 22 taxa. Five taxa had multiple ploidy levels. First estimates of GS were obtained for 16 taxa. A comprehensive review of chromosome number and DNA-ploidy levels in 129 taxa of the section revealed that all taxa have x = 8, except A. rupestre with two polyploid series (x = 8, descending dysploidy x = 7), unique for this section. Diploid taxa dominated (72.1%), while di- & polyploid (12.4%) and exclusively polyploid (15.5%) taxa were less common. Ploidy diversity showed that diploid taxa dominated in the eastern Mediterranean and decreased towards the west and north, whereas only polyploid cytotypes of di- & polyploid taxa or exclusively polyploid taxa dominated in northern and northwestern Europe. A 4.1-fold variation in GS was observed across 33 taxa analysed so far (2C = 22.3-92.1 pg), mainly due to polyploidy, with GS downsizing observed in taxa with multiple ploidy levels. Intra-sectional GS variation suggests evolutionary relationships, and intraspecific GS variation within some taxa may indicate taxonomic heterogeneity and/or historical migration patterns. CONCLUSIONS: Our study showed advantages of FCM as an effective tool for detecting ploidy levels and determining GS within the section. GS could be an additional character in understanding evolution and phylogenetic relationships within the section.
Keywords: DNA ploidy level; Flow cytometry; Polyploidy; Cytogeography; Chromosome number; Genome size